Interactions of ethanol with friction modifiers in model engine lubricants - Costa,H; Spikes,H (Lubricants, 2019)
When employed as an engine fuel, ethanol can accumulate in the lubricant during use. Previous work has shown that ethanol contamination affects friction and elastohydrodynamic lubrication (EHL) film formation, and also the growth and stability of anti-wear tribofilms. The present work uses spacer-layer ultrathin interferometry and MTM tests to investigate how ethanol (both hydrated and anhydrous) interacts with friction modifiers in model lubricants. Small proportions (5 wt %) of ethanol were added to solutions of friction modifiers (one MoDTC and three organic friction modifiers) in a Group I base oil. For the three organic friction modifiers, the presence of ethanol promoted the formation of thick viscous boundary films so that very low friction coefficients were measured at low entrainment speeds. For the MoDTC additive, the presence of ethanol prevented the formation of a low friction film at low speeds at 70 °C, but this effect disappeared at 100 °C, probably due to ethanol evaporation.